Estimating Fed's unconventional policy shocks - Marek Jarociński (European Central Bank (ECB), 2021)
Fed's monetary policy announcements convey a mix of news about different kinds of conventional and unconventional policies and about the economy. Financial market responses to these announcements are very leptokurtic: often tiny, but sometimes large. I estimate the underlying structural shocks exploiting this feature of the data. I find standard monetary policy, Odyssean forward guidance, large scale asset purchases and Delphic forward guidance, and estimate their effects.
Keywords: E52; E58; E44; 330; High-frequency identification; Non-Gaussianity; Excess kurtosis; Forward guidance; Asset purchases